2018
DOI: 10.1093/teamat/hry009
|View full text |Cite
|
Sign up to set email alerts
|

Learning to teach contextualized problem-solving in a non-calculus mathematics pathway

Abstract: We report on the professional learning of a small purposive sample of teachers beginning to teach an English post-16 mathematics course centred around contextualised problem solving. We describe their accounts of change, their intentions and justification for those, and how development was supported. The demands of the course require 'boundary crossing' between contexts and mathematics that was novel for these teachers and their students, and learning to teach for such approaches is known to be demanding. By d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…However, there is some evidence that given appropriate subject-specific and generic foundations (the precise nature and extent of which are yet to be established), together with sufficient time, goal-related dispositions and appropriate access to expertise, some of which might be peercollaborative, experienced teachers are often able to develop in new directions and depths in semiautonomous ways (e.g. Chan et al, 2018;Golding, Smith and Blaylock, 2018).…”
Section: Expertise For Teaching Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some evidence that given appropriate subject-specific and generic foundations (the precise nature and extent of which are yet to be established), together with sufficient time, goal-related dispositions and appropriate access to expertise, some of which might be peercollaborative, experienced teachers are often able to develop in new directions and depths in semiautonomous ways (e.g. Chan et al, 2018;Golding, Smith and Blaylock, 2018).…”
Section: Expertise For Teaching Mathematicsmentioning
confidence: 99%
“…Chan et al 2018) and from opportunities to work collaboratively with expert others, supported by bespoke time and moderate funding (e.g. Golding, Smith and Blaylock, 2018).…”
Section: Expertise For Teaching Mathematicsmentioning
confidence: 99%
“…The overall aim of this paper, then, is to investigate quantitatively students' experiences of Core Maths in the wider context of a compulsory pre-16 mathematics curriculum that has generally been regarded as quite alienating to a large proportion of students (Brown et al, 2008). The findings of this research will contribute to the growing evidence base (Homer et al, 2018;Golding et al, 2018;Mathieson et al, 2020) focused on whether Core Maths is likely to provide a successful post-16 pathway in mathematics -in terms of uptake, attainment, mathematical capability and so on -for the large number of potential students for whom it was designed. It also adds to the international evidence on the impact new mathematics curricula can have on student experiences and attitudes to mathematics.…”
Section: The Aims Of the Current Papermentioning
confidence: 97%
“…In contrast, more transmissionist teaching approaches are those that are typically more teacher-centred, where mathematics teaching is broadly conceived as a set of rules that are to be passed on to students (Swan, 2006). The evidence suggests that transmissionist approaches to mathematics teaching are commonly practised in English compulsory schooling, both preand post-16 (Pampaka et al, 2012;Smith, 2017;Golding et al, 2018).…”
Section: Pedagogical Approaches To the Teaching Of Mathematicsmentioning
confidence: 99%
“…When the literature related to mathematics education was reviewed, it was seen that using real life problems (Golding, Smith & Blaylock, 2018), modelling activities (Park, Park, Park, Cho & Lee, 2013;Arzarello, Ferrara & Robutti, 2012) and technological software (Driver, 2012;Camacho, Depool & Santos-Trigo, 2009) lead to increase in academic achievement or positive improvement in conceptual understanding. Research have shown that in the teaching process of integral concept, software (Sevimli, 2013;Heid, 2003) such as Computer Algebra System and Geogebra, daily life problems and multiple representations (Sealey, 2008), and modelling activities were used.…”
Section: Introductionmentioning
confidence: 99%